Financial constraints and cash holdings in private firms: Evidence from discontinuous credit ratings - Oliver Enigst; Emil Bustos (Research Institute of Industrial Economics (IFN), 2024)
We study how financing constraints affect the cash holdings of small and mediumsized enterprises. There has been little empirical work on this topic, even though these firms often face financial constraints. We contribute by using detailed data on credit ratings in Sweden as a measure of financial constraints. We then use panel regressions and a regression-discontinuity analysis to estimate the relationship between access to credit and cash holdings. Our analysis finds no causal effect of credit ratings on cash holdings.
Keywords: D22; D25; G32; 330; Financial Constraints; Cash; Private Firm; Credit Score